2022
DOI: 10.5395/rde.2022.47.e2
|View full text |Cite
|
Sign up to set email alerts
|

How do imaging protocols affect the assessment of root-end fillings?

Abstract: Objectives This study investigated the impact of micro-computed tomography (micro-CT)-based voxel size on the analysis of material/dentin interface voids and thickness of different endodontic cements. Materials and Methods Following root-end resection and apical preparation, maxillary premolars were filled with mineral trioxide aggregate (MTA), Biodentine, and intermediate restorative material (IRM) ( n = 24). The samples were scanned using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In a recent noteworthy study, Torres et al [45] found that the evaluated cements demonstrated a decrease in the void percentage when a greater voxel size was used. These discrepancies occurred since the micro-CT images are limited by the dimensions of the target object.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a recent noteworthy study, Torres et al [45] found that the evaluated cements demonstrated a decrease in the void percentage when a greater voxel size was used. These discrepancies occurred since the micro-CT images are limited by the dimensions of the target object.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, this disparity may be due to the lack of standard assessment methods. In a research series, Torres et al [43][44][45] investigated the impact of various factors on the accuracy of the quantitative measurement of the porosity volume in CSCs by micro-CT, such as voxel size, image-processing software, and the radiopacity of the material. According to the authors [45], smaller voxel sizes are preferable for evaluating both the thickness of materials and the volume of interfacial voids produced by them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation